A complexidade da coda silábica na escrita de pré-escolares - Cardoso, Monique Herrera [UNESP] (2010)
This article investigated syllabic coda in Brazilian pre-school children writing. Data were collected from texts produced by 5 to 6-year-old children who attended a public pre-school in a city from São Paulo state. The results showed that: (1) 52,14% of graphemes were omitted; (2) from the remaining 47, 86%, 61, 39% were in accord to orthographic rules and 38, 61% corresponded to orthographic substitutions; (3) omissions and substitutions varied based on the kind of coda: nasals had smaller percentage of omissions and higher percentage of substitutions; the opposite occurred in thrills and fricatives; (4) there was no direct influence of stress over omissions, substitutions and conventional writing of graphemes. The high percentage of omissions point out the coda complexity in children’s writing, such as it was already observed in spoken language. As for the substitutions, they seem to occur due to the different possibilities of registering the coda in Portuguese writing, what explains why nasals substitutions had higher percentage than fricatives and thrills. As the stress had no influence over writing of codas, we could suppose that children base their writings not only on information that they acquire from spoken utterances, but also on written utterances with which they deal with in their literacy activities. This complexity suggests that erros in writing must not be considered as cues of children’s learning difficulties, but as cues of relationships they establish between their orthography and the complexity of the language itself.